Radiolabeled tirofiban – a potential radiopharmaceutical for detection of deep venous thrombosis - Darkovska-Serafimovska M; Janevik-Ivanovska E; Djorgoski I; Arsova-Sarafinovska Z; Zdravkovska M; Balkanov T; Ugresic N (Dove Medical Press, 2016)
Marija Darkovska-Serafimovska,1,2 Emilija Janevik-Ivanovska,1 Icko Djorgoski,2 Zorica Arsova-Sarafinovska,1,3 Milka Zdravkovska,1 Trajan Balkanov,4 Nenad Ugresic5 1Department of Pharmacy, Faculty of Medical Sciences, Goce Delcev University, Stip, 2Department of Physiology, Faculty of Natural Sciences and Mathematics, Ss Cyril and Methodius University in Skopje, 3Department of Quality Control of Medicines, Institute for Public Health of the Republic of Macedonia, 4Department of Pharmacology and Toxicology, Faculty of Medicine, Ss Cyril and Methodius University in Skopje, Skopje, Republic of Macedonia; 5Department of Pharmacology, Faculty of Pharmacy, University of Belgrade, Belgrade, Serbia Aim: The aim of this study was to investigate the possibility of using 99mtechnetium (99mTc)-labeled tirofiban (a reversible antagonist of glycoprotein IIb/IIIa) for detection of deep venous thrombosis (DVT) in rats without causing an antiplatelet effect.Methods: The ability of in vitro tirofiban to inhibit adenosine 5'-diphosphate (ADP)-induced platelet aggregation was evaluated using optical aggregometer. Binding of 99mTc-tirofiban to platelets was evaluated. Serum levels of unlabeled (a validated high performance liquid chromatography method) and 99mTc-tirofiban after single intravenous injection were evaluated in male Wistar rats with or without induced DVT (femoral vein ligation model), and the rats were also subjected to whole body scintigraphy.Results: Tirofiban in vitro inhibits ADP-induced aggregation of human platelets in a dose- and concentration-dependent manner (10 nM to 2 µM), but only if it is added before ADP and not after ADP. 99mTc labeling did not affect the ability of tirofiban to bind to either human or rat platelets, nor did it affect tirofiban pharmacokinetics in intact rats or in animals with induced DVT. When 99mTc-tirofiban was injected to rats after induction of DVT, at a molar dose lower than the one showing only a weak antiaggregatory effect in vitro, whole body scintigraphy indicated localization of 99mTc-tirofiban around the place of the induced DVT.Conclusion: 99mTc labeling of tirofiban does not affect its ability to bind to glycoprotein IIb/IIIa or its in vivo pharmacokinetics in rats, either intact or with DVT. A low, nonantiaggregatory dose of 99mTc-tirofiban may be used to visualize DVT at an early stage. Keywords: tirofiban, 99mtechnetium, deep venous thrombosis, visualization